2017
DOI: 10.15835/buasvmcn-vm:0052
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens Contamination Level Reduction on Beef Using Organic Acids Decontamination Methods

Abstract: In this study we aimed to assess the efficiency of organic acids in different concentrations regarding pathogens as Salmonella, Listeria and Escherichia on beef, which can cause food borne illness in humans. The samples were sterilized using UV radiation for 30 minutes, afterwards being contaminated with 1 ml of microbial suspension (0.5 MacFarland). We used reference bacterial strains for Salmonella Enteritidis, Escherichia coli and Listeria monocytogenes. The samples were subjected to decontamination procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Immediately after treatment, the E. coli O157:H7 count in the C, SDW and 1%AA groups were significantly (p < .05) higher compared to the other groups (5%AA, 1%CA, 5%CA, 1%LA and 5% LA). In a similar manner, in previous studies, it has been reported that the use of different concentrations of organic acids in different kinds of foods caused a decrease in the population of E. coli O157:H7 (Choi et al, 2009;Dan et al, 2017;Harris et al, 2012;Kalchayanand et al, 2012;Mohan & Polman, 2016;Tajkarimi & İbrahim, 2011;Thomas et al, 2020).…”
Section: Re Sults and Discussionsupporting
confidence: 69%
“…Immediately after treatment, the E. coli O157:H7 count in the C, SDW and 1%AA groups were significantly (p < .05) higher compared to the other groups (5%AA, 1%CA, 5%CA, 1%LA and 5% LA). In a similar manner, in previous studies, it has been reported that the use of different concentrations of organic acids in different kinds of foods caused a decrease in the population of E. coli O157:H7 (Choi et al, 2009;Dan et al, 2017;Harris et al, 2012;Kalchayanand et al, 2012;Mohan & Polman, 2016;Tajkarimi & İbrahim, 2011;Thomas et al, 2020).…”
Section: Re Sults and Discussionsupporting
confidence: 69%
“…While meat decontamination is continuously investigated globally, by the end of 2020, few countries had developed guidelines or regulations that dealt with carcass decontamination during slaughter [27][28][29][30]32]. As noted by [31], developing countries typically rely on the guidelines of the Food and Agriculture Organization (FAO) when applying carcass decontamination programs.…”
Section: Resultsmentioning
confidence: 99%
“…Acetic acid (AA) is another organic acid extensively used in the food industry. In addition to its preservation capabilities, AA can be used to kill or reduce other microorganisms of interest in food or meat products [27,28]. Researchers have argued that while the use of AA in its concentrated form could be beneficial in reducing microorganisms, its strong pungent smell could be a deterrent to its usage on fresh carcasses [10,29].…”
Section: Acetic Acid Treatmentmentioning
confidence: 99%
“…and E. coli. For Salmonella spp., and for a 3% concentration, after 30 min of inoculated, there were reductions of 2.34 and 2.35 log CFU/g were obtained for lactic and citric acid, respectively [9].…”
Section: Influence Of Organic Acids On Salmonella Spp Counts Over Timementioning
confidence: 91%